Research on Deformation Mechanism of Retracement Channel during Fully Mechanized Caving Mining in Superhigh Seam. (24th December 2018) - Fei, Liu; Jiang, Zhongxi
Abstract : The multichannel retracement in the auxiliary laneway has become one of the key technologies in the high-yield and high-efficiency production of large and extra-large coal mines in western China. For the successful application of this technology, the control of retracement channel deformation is decisive. This paper takes the support of the retracement channel in full-mechanized caving working surface of Mentai Buliangou Coal Mine as the engineering background. In view of the occurrence characteristics of thin bedrock, thick unconsolidated layer and superhigh seam, theoretical analysis, numerical calculation, and field industrial test are adopted. The deformation rules and stress distribution characteristics of the surrounding rock as well as the changes of the support structure in the retracement channel during the end mining on the full-mechanized caving working surface are systematically studied, and the deformation and failure mechanism of the surrounding rock is revealed. The field measurement shows that the adoption of optimal design scheme can effectively control the deformation of the surrounding rock in the retracement channel during the end mining period and consequently address the problem of rapid moving of the working surface, which is significant for engineering practices.